Theoretical study of the interaction between the antibiotic linezolid and the active site of the 50S ribosomal subunit of the bacterium Haloarcula marismortui - Grandini, Giulia Saneti [UNESP]; Morgon, Nelson Henrique; de Souza, Aguinaldo Robinson [UNESP] (Wiley, 2024)
First antibiotic in the oxazolidinone class, linezolid fights gram-positive multiresistant bacteria by inhibiting protein synthesis through its interaction with the 50S subunit of the functional bacterial ribosome. For its antimicrobial action, it is necessary that its chiral carbon located in the oxazolidinone ring is in the S-conformation. Computational calculation at time-dependent density functional theory methodology, ultraviolet–visible (UV–Vis), and electronic circular dichroism spectra was obtained for noncomplexed and complexed forms of linezolid to verify the possible chirality of nitrogen atom in the acetamide group of the molecule. The molecular system has two chiral centers. So, there are now four possible configurations: RR, RS, SR, and SS. For a better understanding of the system, the electronic spectra at the PBE0/6-311++G(3df,2p) level of theory were obtained. The complexed form was obtained from the crystallographic data of the ribosome, containing the S-linezolid molecular system. The computational results obtained for the electronic properties are in good agreement with the experimental crystallographic data and available theoretical results.
Keywords: computational chemistry; linezolid; NCIPLOT4; receptor–ligand interactions; TD-DFT; UV-ECD